2012
DOI: 10.1242/jcs.102574
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mid1 domains for targeting and scaffolding in fission yeast cytokinesis

Abstract: SummaryDivision-site selection and contractile-ring assembly are two crucial steps in cytokinesis. In fission yeast, the anillin-like Mid1 protein specifies the division site at the cell equator by assembling cortical nodes, the precursors of the contractile ring. Thus, Mid1 is essential for linking the positional cues for the cleavage site to contractile-ring formation. However, how Mid1 domains cooperate to regulate cytokinesis is poorly understood. Here we unravel the functions of different Mid1 domains (mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 61 publications
(145 reference statements)
2
48
0
Order By: Relevance
“…One possible mechanism is that Cdc15p is a physical link between the plasma membrane and the contractile ring, given that it interacts with contractile ring proteins (Carnahan and Gould, 2003; Laporte et al, 2011; Lee and Wu, 2012; Roberts-Galbraith et al, 2009) as well as membrane lipids (Takeda et al, 2004). While this may be true, our observations on cells with mutated or depleted Cdc15p revealed that the underlying defect responsible for contractile ring sliding is slow transfer of β-glucan synthetase Bgs1p (and perhaps other proteins) from the Golgi apparatus to the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…One possible mechanism is that Cdc15p is a physical link between the plasma membrane and the contractile ring, given that it interacts with contractile ring proteins (Carnahan and Gould, 2003; Laporte et al, 2011; Lee and Wu, 2012; Roberts-Galbraith et al, 2009) as well as membrane lipids (Takeda et al, 2004). While this may be true, our observations on cells with mutated or depleted Cdc15p revealed that the underlying defect responsible for contractile ring sliding is slow transfer of β-glucan synthetase Bgs1p (and perhaps other proteins) from the Golgi apparatus to the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…We carried out IP assays and Western blotting as previously described [63,7173]. Briefly, GFP-tagged protein expressed at its endogenous level was pulled down from S .…”
Section: Methodsmentioning
confidence: 99%
“…If the standard can be distinguished from the protein of interest, it is desirable to include cells that express the standard and experimental fusion proteins on the same slide to ensure comparable illumination. If the standard is not distinguishable, images can be taken consecutively or another marker can be imaged separately to distinguish the control cells [27,34] as long as the two fluorophores are sufficiently distant to eliminate Förster resonance energy transfer (FRET). One advantage of this method is that a much greater number of protein molecules can be counted than with the photobleaching method.…”
Section: Quantification By Ratio Comparison To Fluorescent Standardsmentioning
confidence: 99%